2016
DOI: 10.1002/ajoc.201600159
|View full text |Cite
|
Sign up to set email alerts
|

π–π Interactions: Influence on Molecular Packing and Solid‐State Emission of ESIPT and non‐ESIPT Motifs

Abstract: Novel, triphenylamino benzothiazole-based excited-state intramolecular protont ransfer (ESIPT) and non-ESIPT fluorophores were prepared by Suzuki coupling reactions. Their photophysical properties in solution,a queous suspension,a nd in the solids tate were systematically investigated. High fluorescenceq uantum efficiencies (F sol % 95 %; F solid % 88 %), moderate Stokes shifts ( % 8000 cm À1 ), microenvironment-sensitive and molecular-framework-dependent emission are the striking features of the protocol desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…As reported in our earlier communications, solid/aggregated states could be achieved by suppressing non‐radiative pathways. Various donor (aromatic amines) and acceptor (azoles, triazoles, diazole) groups have been reported in the past .…”
Section: Introductionsupporting
confidence: 63%
“…As reported in our earlier communications, solid/aggregated states could be achieved by suppressing non‐radiative pathways. Various donor (aromatic amines) and acceptor (azoles, triazoles, diazole) groups have been reported in the past .…”
Section: Introductionsupporting
confidence: 63%
“…Yamato et al . and Hariharan et al . have shown that strong π–stacking interactions can lead to extensive excimer formation in the solid state/thin films with a consequent reduction in the fluorescence quantum yield.…”
Section: Resultsmentioning
confidence: 99%
“…The quenching of fluorescence can be attributed to the supramolecular arrangement of (I) in the crystal structure that involves one of the cyanophenyl rings in weak face-to-facedisplacedinteractions [centroid-centroid distance = 4.54 Å , slippage = 2.96 Å and dihedral angle between planes = 0.0 ] (Fig. 3) (Kupcewicz & Małecka, 2015;He et al 2015;Padalkar et al, 2016).…”
Section: Figurementioning
confidence: 99%